2020
DOI: 10.1186/s40634-020-00294-y
|View full text |Cite
|
Sign up to set email alerts
|

Discoid lateral meniscus: importance, diagnosis, and treatment

Abstract: Discoid lateral meniscus (DLM) is a common anatomic variant in the knee typically presented in young populations, with a greater incidence in the Asian population than in other populations. As DLM is a congenital anomaly, the ultrastructural features and morphology differ from those of the normal meniscus, potentially leading to meniscal tears. Snapping and pain are common symptoms, with occasional limitations of extension, in patients with DLM. Examination of the contralateral knee is necessary as DLM affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 70 publications
0
49
0
4
Order By: Relevance
“…Furthermore, the use of fibrin clot augmentation has been described in the literature, particularly in cases exhibiting concurrence of horizontal or transverse tear. 12 In this study, even if meniscal displacement was observed, localized peripheral longitudinal tears tended to be repairable, while those with peripheral tears covering the entire meniscus and those with severe defects or tears in the body of the meniscus tended to be difficult to repair. In terms of postoperative outcomes, in addition to subtotal meniscectomy, those with residual peripheral rim of 5 mm width or less and those that cannot maintain the hoop function of the meniscus have been reported to show predisposition to concurrent degenerative changes or OCD.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, the use of fibrin clot augmentation has been described in the literature, particularly in cases exhibiting concurrence of horizontal or transverse tear. 12 In this study, even if meniscal displacement was observed, localized peripheral longitudinal tears tended to be repairable, while those with peripheral tears covering the entire meniscus and those with severe defects or tears in the body of the meniscus tended to be difficult to repair. In terms of postoperative outcomes, in addition to subtotal meniscectomy, those with residual peripheral rim of 5 mm width or less and those that cannot maintain the hoop function of the meniscus have been reported to show predisposition to concurrent degenerative changes or OCD.…”
Section: Discussionmentioning
confidence: 52%
“…11 Therefore, when there is a considerable defect in the popliteal hiatus of the DLM and reduction with a probe is unachievable, subtotal menisectomy is considered as a viable option, albeit with reluctance. 12 In addition, those with displacement are prone to require subtotal meniscectomy than those without displacement, and among those with displacement, the central shift type has been reported to most commonly require subtotal menisctomy. 9 In this study, when the meniscal body was The Lysholm score improved from a mean of 65.4 points preoperatively to 95.2 points postoperatively in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…3 Expansion of this field is developing fast, thanks to advancements in arthroscopic technology, increasing surgeon comfortability, and growing knowledge of child joint pathology. 4 While knee arthroscopy is used in children and adolescents to treat intra-articular fractures, 5 osteochondritis dissecans, 6 discoid lateral meniscus, 7 and synovitis, 8 the most common indications include sport injuries of the meniscus and ACL. 9 The incidence of acute and overuse sport injuries in pediatric athletes is at an all-time high, given the rise in sport participation.…”
Section: Discussionmentioning
confidence: 99%
“…The discoid meniscus has an abnormal shape and structure. The disintegration of the circular collagen fibre system in the discoid meniscus matrix may be responsible for the higher tear rate and higher degeneration of the discoid meniscus compared to the normal meniscus [ 1 ]. Clinically, compared with the discoid medial meniscus, discoid lateral meniscus (DLM) is the most common, with a high prevalence in Asian populations (16–20%) [ 2 , 3 ]; and bilateral DLM accounts for 79–97% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic DLM is characterized by pain, swelling, snapping, locking, knee instability and limited mobility [ 5 ], which is mainly diagnosed by magnetic resonance imaging (MRI) and treated by arthroscopic surgery [ 3 , 6 ]. Although the overall postoperative outcomes of symptomatic DLM are acceptable [ 1 , 5 , 7 , 8 ], the outcomes between individuals are still largely different, which may result from diversity in patient’s characteristics and treatments [ 6 ]. Currently, studies have reported the influencing factors of postoperative arthroscopy for symptomatic DLM, but the results are inconsistent possibly resulted from differences in sample size, studied factors, and knee function evaluation system, etc.…”
Section: Introductionmentioning
confidence: 99%